Multimodal Comprehension of Language and Graphics: Graphs with and without annotations - Cengiz Acarturk; Christopher Habel; Kursat Cagiltay; Ozge Alacam (Bern Open Publishing, 2008)
An experimental investigation into interaction between language and information graphics in multimodal documents served as the basis for this study. More specifically, our purpose was to investigate the role of linguistic annotations in graph-text documents. Participants were presented with three newspaper articles in the following conditions: one text-only, one text plus non-annotated graph, and one text plus annotated graph. Results of the experiment showed that, on one hand, annotations play a bridging role for integration of information contributed by different representational modalities. On the other hand, linguistic annotations have negative effects on recall, possibly due to attention divided by the different parts of a document.